Educational Intervention of Oral Cancer Screening to Indonesian General Dentists - Dr Elizabeth Sari; Professor Nicola Cirillo; Professor Michael McCullough (Elsevier, 2023)
Aim or Purpose: General dental practitioners (GDPs) play a vital role as front-line health professionals in oral cancer (OC) screening. Therefore, our study aimed to assess GDPs' knowledge of OC and to improve participants' skills in performing OC screening. Materials and Methods: This was a cross-sectional study using a pre- and post-training questionnaire and was undertaken between June 2022 to January 2023. The training intervention was delivered with a hybrid method of theory and practical based. The study was conducted in Banda Aceh (BA), Surabaya (SBY), Yogyakarta (YG), West Papua (WP), West Kalimantan (WK), and North Sumatra (NS), however, GDPs from 18 different provinces enrolled. Ethical approval was gained from Indonesia and Australia. ANOVA, Chi-Square, Likert scale and logistic regression were used to determine the difference between means, with 95% CI and P < 0.05. Results: 323 GDPs registered, with preponderance from NS (n=83), followed by YG (59), WK (n=57), WP (n=41), SBY (n=36), BA (n=23), and the remainder (n=27) from other regions, with a total of 170 (52.14%) GDPs sent back their post-training questionnaire. After the training, 26.5% increased number of GDPs who felt they had sufficient knowledge of OC risk factors and 68.72% increased number of GDPs who reported they could differentiate precursor lesions. A large proportion of dentists (168 out of 170) self-reported that their confidence was significantly increased. Conclusions: The training intervention has significantly improved GDPs' knowledge and confidence in preforming OC screening. Therefore, we suggest that this training can be implemented as a part of curriculum of Dental Schools and should be offered as a continuing professional development program.